Multimedia Pembelajaran Pada Mata Pelajaran Teknik Instalasi Tenaga Listrik (TITL) kelas X - Ismawati Ismawati; Juhaidatur Rahmi; Johan Eka Wijaya DN; Joko Kuswanto (Universitas Baturaja, 2025)
This research aims to develop learning multimedia in the subject of Electrical Power Installation Engineering (TITL) class X at Vocational High Schools (SMK). The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of validation by experts show that the multimedia product developed is very feasible to use with the criterion of